(untitled) (Modern education and development, 2025)
This article discusses artificial intelligence (AI) as one of the central directions of technological development in recent years. The development of AI technologies is leading to profound changes in various areas of society. Its main goal is to simulate human mental activity, as well as to help solve complex problems. Understanding the role of AI systems in society, their tasks and prospects is important not only from a technological, but also from a social, economic and ethical perspective.